NEW SCIENTIFIC-TECHNICAL DEVELOPMENTS FOR MODERNIZATION AND TECHNICAL RETOOLING OF FOUNDRIES - A. P. Melnikov; M. A. Sadoha (Литьë и металлургия, 2011)
New scientific and technical developments of OAO «BELNIILIT» for modernization and technical re-equipment of foundries are given.